Korelasi antara Nilai HbA1c dengan Kadar Kreatinin pada Pasien Diabetes Mellitus Tipe 2 - Zulfian Zulfian; Ika Artini; Rifqi Ihsaan Maulana Yusup (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Diabetes mellitus (DM) is a chronic metabolic disorder caused by decreased insulin production or effectively produced insulin resistance. Insulin is a hormone to regulate blood sugar levels. With the development of the era of many food choices and unhealthy lifestyles spread throughout the community, this has led to an increase in the number of degenerative diseases and type 2 diabetes is one of the degenerative diseases. This study was to determine the correlation between HbA1c values ​​and creatinine levels in type 2 diabetes mellitus patients. This study used a quantitative method with a correlative analytic design with a cross-sectional approach. The subjects in the study were 48 patients. The instrument used was medical record data. The results of statistical analysis using the Spearman correlation test showed a p-value of 0.021 (p-value <0.05) which means that there was a significant correlation with the strength of a moderate positive correlation between HbA1c values ​​and creatinine levels in type 2 diabetes mellitus patients at Pertamina Bintang Hospital Amin Bandar Lampung in 2019. There is a correlation between HbA1c values ​​and creatinine levels in type 2 Diabetes Mellitus patients at Pertamina Bintang Amin Hospital in Bandar Lampung in 2019.